Low-level laser therapy stimulates tissue repair in the temporomandibular joint of obese rats subjected to orthodontic movement (Research, Society and Development, 2025)
The aim of this study was to evaluate the effects of low-level laser therapy on histological changes in the temporomandibular joint caused by induced tooth movement in obese rats. Forty male Wistar rat pups were used; thirty pups received subcutaneous injections of 4 g/kg/day of monosodium glutamate (obese animals - MSG) in the cervical region during the first five days of life, and ten received injections of hyperosmotic saline solution, 1.25 g/kg/day (control animals - CTL). Four experimental groups were formed (n=10/group): Group 1: Control (CTL), rats that were not subjected to any experimental procedure; Group 2: obese rats without induced tooth movement (MSG); Group 3: obese rats that were subjected to induced tooth movement (MDI) (MSG + MDI); Group 4: obese rats that underwent MDI and LTBP (MSG + MDI + LTBP). At 90 days, the induced tooth movement device (MDI) was installed in groups 3 and 4. At 91 days, low-level laser treatment was started. At 97 days of the experiment, the animals were weighed, measured and sacrificed. The temporomandibular joints (TMJ) on the right side were removed, fixed and processed for histology. The animals in the obese group treated with low-level laser therapy (MSG + MDI + LTBP) showed reduced articular disc thickness and hyperplasia and vascularization of the TMJ synovial membrane. We conclude that low-level laser therapy is effective in treating histological changes in the TMJ caused by orthodontic movement in rats with hypothalamic obesity.